Impaired Inhibitory Control of Saccadic Eye Movements in Cervical Dystonia: An Eye‐Tracking Study. Issue 5 (8th January 2021) - Carbone, Federico; Ellmerer, Philipp; Ritter, Marcel; Spielberger, Sabine; Mahlknecht, Philipp; Hametner, Eva; Hussl, Anna; Hotter, Anna; Granata, Roberta; Seppi, Klaus; Boesch, Sylvia; Poewe, Werner; et al.
Abstract: Background: The pathophysiology of cervical dystonia is still unclear. Recent evidence points toward a network disorder affecting several brain areas. The objective of this study was to assess the saccadic inhibition as a marker of corticostriatal function in cervical dystonia. Methods: We recruited 31 cervical dystonia patients and 17 matched healthy controls. Subjects performed an overlap prosaccade, an antisaccade, and a countermanding task on an eye tracker to assess automatic visual response and response inhibition. Results: Cervical dystonia patients made more premature saccades ( P = 0.041) in the overlap prosaccade task and more directional errors in the antisaccade task ( P = 0.011) and had a higher rate of failed inhibition in the countermanding task ( P = 0.001). Conclusions: The results suggest altered saccadic inhibition in cervical dystonia, possibly as a consequence of dysfunctional corticostriatal networks. Further studies are warranted to confirm whether these abnormalities are affected by the available therapies and whether this type of impairment is found in other focal dystonias. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.